(untitled) (Research, Society and Development, 2022)
Currently the most of the Coffea canephora cultivars, developed and recommended by the research, are propagated vegetatively, being popularly known as clonal varieties and/or cultivars. However, those propagated by seeds present a wide genetic base with greater variability of the plants in the crops. Thus, the objective was to characterize a population (genotypes) from C. canephora cultivar ’ES8152’, of seminal propagation, from agronomic characteristics vegetative vigor and canopy height, SPAD readings and vegetation index, after the first harvest in 2022. The planting was carried out in 2019, in an augmented block design with three replications, 240 genotypes and four clonal witnesses (A1, LB1, V8 and V12), being possible to evaluate 199 genotypes, including the witnesses. Data were analyzed by the method of restricted maximum likelihood and best linear unbiased prediction, cluster analysis and genetic correlation networks. The conilon coffee population showed wide genetic variability. The characterization allowed the identification of promising ones, such as genotypes 16, 25, 82 and 173. The genetic correlations were positive, significant and higher between the pairs vegetative vigor x canopy height and SPAD readings x vegetation index. Most of the genotypes evaluated showed intermediate vegetative vigor, combined with low vegetative stress. Thus, the adopted strategies were efficient in the characterization of the genotypes, being able to assist in the taking of decisions in the process of breeding of conilon coffee.